MODERN APPROACHES OF RESEARCHING THE PHENOMENON OF SELFPRESENTATION - Chigirin, T. (Continuing Professional Education: Theory and Practice, 2019)
In the article contemporary theories of self presentation are analyzed and compared. The general foundations of reaching successful self presentation are described basing on the study of different mechanisms of this phenomenon. The meaning of selfpresentation was attempted to disclose since a large number of people have a vague idea about it. Today the selfpresentation of personality is a topical scientific problem which is studied in various branches of sciences, such as psychology and pedagogies. Selfpresentation is often understood as the process, when people controls the impression of the social environment by attracting one’s attention and as a result receives satisfaction as motivation, needs and goals of the individual, as well as forming the image of “I” and selfesteem.